Sno2-N-Si Isotype Heterojunction Solar Cell with Efficiency of 7.1% - Sabry, Raad S (Al-Nahrain Journal of Science, 2012)
This paper presents the results of a study of the photovoltaic effect of SnO2/n-Si solar cell formed by chemically sprayed SnO2 on signal crystal silicon the main of using SnO2 chemically sprayed thin films include low cost and the risibility of production in large scale, the photovoltaic characteristics included short circuit current (Jsc), open circuit voltage (Voc), where the maximum (Jsc) and (Voc)obtained at AM1 were 14.3 (mA cm-2) and 630(mV), respectively. The fill factor (FF) was (0.68). Photo-induced open carrier lifetime of these cells is about (29 μs).